Neoadjuvant Intra-Arterial Cytoreductive Chemotherapy for Lacrimal Gland Adenoid Cystic Carcinoma: A Long-Term Follow-up Study of a Trimodal Strategy - Tse, David T.; Benedetto, Pasquale W.; Tse, Brian C.; Feuer, William J. (American journal of ophthalmology, 2022)
To report the therapeutic efficacy of integrating neoadjuvant chemotherapy with conventional bimodal therapies for lacrimal gland adenoid cystic carcinoma by providing an additional 8 years of follow-up data on the same cohort of patients whose cumulative 10-year disease-free survival outcomes were reported in 2013. Non-randomized, retrospective, interventional case series. Nineteen consecutive patients treated with neoadjuvant intra-arterial cytoreductive chemotherapy (IACC), orbital exenteration, chemoradiotherapy, and adjuvant intravenous chemotherapy at a single institution were included. Analyses were undertaken of locoregional recurrences and distant metastases, disease-free survival time, TNM tumor stage at presentation, response to IACC, and prognostic impact of positive resection margins. The main outcome measures were overall survival, disease-free survival, disease relapse, positive tumor resection margins, and tumor stage at presentation. Eight patients with an intact lacrimal artery (group 1), 7 with AJCC stage T4a-c, had significantly better overall survival (87.5% versus 14.3% at 15 years), disease-specific mortality, and recurrences (all < .001, log-rank test) than prior conventionally treated patients from the Bascom Palmer Eye Institute. Group 1 was superior to group 2, patients lacking an intact lacrimal artery, concerning overall survival (P = .042) and recurrence (P = .017), but with no significant difference in disease-specific mortality (P = .23). Group 2 was associated with a significantly lower cause-specific mortality than the institutional comparator group (P = .039). Prior tumor resection with lateral wall osteotomy and failure to adhere to all protocol elements were adverse prognostic factors for suboptimal outcomes. Positive tumor margins increased the risk of all-cause mortality 4.1 times (P = .036, stratified Cox proportional hazards regression) and disease-specific mortality 8.0 times (P = .043, stratified Cox proportional hazards regression) than a patient with negative margins. Extended follow-up supplemented with AJCC staging data supports neoadjuvant IACC as an integral component of a trimodal treatment strategy in patients with an intact lacrimal artery. Protocol elements implemented as designed appear to have improved overall survival and decreased disease relapse in this cohort. This extended long-term IACC dataset suggests that a critical bar of at least 15 years of follow-up is appropriate for assessing the efficacy of current conventional and future globe-sparing bimodal therapies.